Overcoming obstacles to implementing SMS - Jouni Lappalainen (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2017)
This paper discusses obstacles faced in implementing SMS and uses concrete examples to show how to overcome them across all modes of transport (air, maritime, rail and road) in leading countries, particularly ITF member countries. The difficulties and problems in implementing SMS can originate from the specific cultural features of an organisation or an occupation. The cultural features can become either an enabler or a barrier for implementation of the safety management system. By understanding the cultural features better, the difficulties and problems in implementing safety management systems could be resolved. In order to avoid that particular cultural features become a barrier for implementing safety management systems the employees' experience and expertise should be employed in the implementation work more intensively. Key enablers for safety improvements would involve all organisational levels in the identification, discussion and implementation of potential safety issues. New thinking is needed in safety management and, particularly, in incident reporting. Focusing on positive human factors and understanding humans as a resource of successful performance could motivate and encourage employees to report incidents more actively and thus promote rooting of positive safety culture in organisations. No company can manage implementing the safety management system properly using only its own resources. Co-operation of companies is needed and regulatory agencies should provide support for co-operation. The industries' voluntary co-operation programmes have proved to be effective and valuable for overcoming any obstacles in the implementation of safety management systems.
Keywords: 330; Verkehrssektor; Verkehrssicherheit; Arbeitsschutz; Risikomanagement; Unternehmenskultur; OECD-Staaten